Regenerate Cr(VI) Oxidation Bleaching Solution from Wastewater in Process of Oxidation Bleaching of Montan Wax by Indirect Electrochemical Oxidation - Tang, Panpan; Zhang, Huifen; Xiang, Cheng; Wang, Linchao; Li, Baocai (Asian Journal of Chemistry, 2015)
Chromium plays very important role in industry, especially in the process of oxidation bleaching for Montan wax. Chromium(VI) was converted into Cr(III) during this process and it is very difficult to treat the wastewater. In this study, a new indirect electrochemical oxidation method has been used to treat the wastewater from the process of oxidation bleaching of Montan wax to regenerate the oxidation bleaching solution. A series of experiments (5 variation factors at 4 levels) were carried out and an optimized experiment condition was obtained: Current density, 400A/m2; temperature of cell, 55 °C; Cr(III) concentration at anode cell, above 0.5 mol/L; sulfuric acid concentration in cathode cell, 10 % (v/v); and catalyst usage, 10 mL, 1 % (w/w). Under the optimized conditions, high current efficiency and chromium conversion ratio [Cr(III) to Cr(VI)] were obtained, they are higher than reported values. Five cycles of process have been carried out: oxidation bleaching of Montan wax, then treating the wastewater by indirect electrochemical oxidation to regenerate the oxidation bleaching solution. This study provides feasibility for the oxidation bleaching of Montan wax in industry scale at low-cost and industrial wastewater containing chromium would be significantly reduced.